The Analysis of Minerba (Nickel) Governance Law in Indonesia: A Juridical and Historical Review - Antonius Setyadi (Universitas Dharma Wacana, 2022)
This study aims to analyze the Minerba (Nickel) Governance Law in Indonesia from the perspective of juridical and historical. The mining business is an activity in the context of mineral or coal exploitation. It includes the stages of a general investigation, exploration, feasibility study, construction, mining, processing and refining or development and utilization, transportation and sales, as well as post-mining, as contained in the Law – Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. This study uses normative juridical research; namely, research focused on examining the application of rules and norms, as well as literature studies related to the research under study. While the formulation of the problem is: a) How is the regulation of mineral and coal mining businesses from a review of Law Number 3 of 2020 concerning Mineral and Coal Mining; and b) What is the legal protection for mineral and coal mining businesses in Indonesia? The results of the study resulted in conclusions including a) The regulation in mining law has changed, namely Law Number 3 of 2020 concerning Mineral and Coal Mining; and b) Legal protection for mining businesses by the government for the benefit of society and in order to give authority to obtain equal rights before the law. Therefore, it is concluded that the relevant fields to be covered by the law must continue to be developed so that the legal mindset can include knowledge about the social context and the impact of government policies or actions. Good law must offer something more than existing procedural justice. The law must have the ability to be fair, provide equal opportunities, help determine the interests of society and hold on to the achievement of substantial justice